New Insights Into Implications of CTRP3 in Obesity, Metabolic Dysfunction, and Cardiovascular Diseases: Potential of Therapeutic Interventions - Guo, Bei; Zhuang, Tongtian; Xu, Feng; Lin, Xiao; Li, Fuxingzi; Shan, Su-Kang; Wu, Feng; Zhong, Jia-Yu; Wang, Yi; Zheng, Ming-Hui; Xu, Qiu-Shuang; Ehsan, Ullah Muhammad Hasnain; et al. (Frontiers in Physiology, 2020)
Adipose tissue, as the largest endocrine organ, secrets many biologically active molecules circulating in bloodstream, collectively termed adipocytokines which not only regulate the metabolism but also function in many pathophysiology processes. C1q tumor necrosis factor-related protein 3 (CTRP3), a novel members of CTRPs, belongs to adiponectin’s paralogs. CTRP3 has the wide-ranging effects on the glucose/lipid metabolism, inflammation response, and contributes to cardiovascular protection. In this review, we have comprehensively discussed the latest research of CTRP3 in obesity, diabetes, metabolic syndrome and cardiovascular diseases.